ENCONTRÃO CULTURAL 2º EDIÇÃO - RP FORA DA CAIXA - Souza, Jéssica B. R. d.; Terra, Elisa L.; Pereira, Bruna K. G.; Comim, Geovana; Saraiva, Ivana C.; Theodoro, Victor S. (Salão do Conhecimento, 2013)
Resumo